Financial liberalisation in Asia : analysis and prospects - .Brooks, Douglas H. (Development Centre seminars., 1999)
Rapid globalisation has brought substantial benefits to developing Asia, but it has also heightened the risks associated with policy mistakes, weak financial institutions, and problems in corporate and public governance. The 1997 Asian crisis has demonstrated the urgent need to rethink the sequencing and comprehensiveness of financial liberalisation. Would further opening of Asia's financial systems be helpful or counterproductive in fostering financial stability? What structural reforms do emerging economies need to undertake to ensure that capital inflows are transformed into productive investment? Which regulatory and other requirements would have to be attached to further financial liberalisation? And what role should international organisations and the private sector play in crisis resolution.